Food Product Development : Based on Experience. - Side, Catherine (IFT basic symposium series., 2008)
Improve your product development success ratio!. This IFT Basic Symposium is the collective work of a team of seasoned food industry consultants whose experiences and observations provide a "how to" guide of successful product and process development. Their information-packed presentations will deepen and broaden the food technologist's knowledge of food product development to the sphere beyond the laboratory. Authors address the following key components of product development: Managing the Product Development Process, Consumer & Market Research, Making It Happen, Cost & Pricing. A c.